Student’ Perception of Using the Instagram Account @jagobahasacom in Improving Student English Vocabulary at SMEA Muhammadiyah 1 Yogyakarta - Ditha Andini Lausiry; Akmal Akmal (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This research describes the student perception of using Instagram as their supplementary media to improve their vocabulary. The objectives are to figure out how the production of vocabulary was better by using the Instagram account @jagobahasacom based on the result of the pre-test, and post-test, and to analyze the students’ perception of the @jagobahasacom in supporting them in improving their vocabulary based on the theory of Gibson et al. (2019). A qualitative method with in-depth interviews is the method to analyze the research problem. The researcher collected the data at SMEA Muhammadiyah 1 Yogyakarta, specifically in the tenth-grade economics class. The result showed that the students use the Instagram account @jagobahasacom as the primary learning source in supporting their vocabulary ability since Instagram can be used as an enhanced learning experience. The result of the pre-test, and post-test showed the increasing student vocabulary quality was higher than before. Next, most students positively perceive the influence of the Instagram account @jagobahasacom in their learning outcomes.